Comparative in-vitro pathogenesis of Pasteurella multocida B:2 infection in buffalo - Puspitasari, Yulianna (2020)
Haemorrhagic septicaemia (HS) is a septicaemic disease caused by Pasteurella multocida serotype B:2. It leads to outbreaks with high mortality among cattle and buffalo. The organism enters the host via inhalation or oral routes since P. multocida B:2 has been isolated in both the nasopharynx and intestine of dead cattle and buffaloes. Furthermore, urinary tract was also revealed to play significant role in the development and transmission of HS. Thus, understanding the interactions of P. multocida B:2 with the host cells at the point of entry and excretion, and at the endothelial cells that leads to severe damage and destruction are important. Subsequently, following entrance into blood circulation, survival of P. multocida B:2 against phagocytic cells to overwhelm the host is critical. There are few studies involving in-vitro pathogenesis but none was done using buffalo cells, organs or tissues. Since buffalo is more susceptible to HS, this study uses buffalo for evaluating the attachment and distribution of P. multocida B:2 onto cells of respiratory and urinary tracts, the survival of P. multocida B:2 in phagocytic cells and the severity of endothelial cell damage by P. multocida B:2. To achieve these objectives, explants from the repiratory and urinary tracts were prepared and challenged with P. multocida B:2, the neutrophil and macrophage were harvested and culture before challenge while the endothelial monolayers were prepared and similarly challenged. The attachment and distribution, survival within phagocytic cells, and endothelial destruction were determined using a scoring system. Three healthy buffaloes with no history of vaccination against haemorrhagic septicaemia were killed before the lung and bladder explants were prepared. The explants were then challenged with 109 cfu/ml of live P. multocida B:2. At the same time, a known septicaemic organism, Escherichia coli and a known respiratory organism, Mannhaemia haemolytica A:2 were used as comparison, since HS is a septicaemic disease and the respiratory tract is the preferred sites r P. multocida B:2. The explants were harvested at 2-h intervals until 12 hours before the rate of attachment was scored using scanning electron microscopy while the distribution was determined using immunoperoxidase staining. All bacterial strains showed similar attachment and distribution patterns. Pasteurella multocida B:2 and M. haemolytica A:2 showed significantly (p<0.05) increasing attachment and distribution with time to reach peak at 8-10 h and 12 h post-inoculation, respectively. On the other hand, E. coli showed significantly (p<0.05) increasing attachment and distribution with time to reach peak at 12 h post-inoculation. There were significant (p<0.05) correlations between the rate of attachment and distribution of all bacteria. In general, the attachment and distribution of P. multocida B:2 in the lungs and urinary bladder of buffalo were much better than the known respiratory bacterium, the M. haemolytica A2, and as good as the known septicaemic bacterium, the E. coli. Therefore, P. multocida B:2 is, in fact, a septicaemic bacterium with high potential of causing septicaemic disease. Neutrophils and monocytes were harvested from healthy buffaloes to evaluate the in-vitro efficacy of phagocytosis and bacterial killing. The neutrophils were prepared as cell culture while the monocytes were allowed to mature into macrophages before being prepared as cell culture. These cells were divided into 3 groups. Group 1 was inoculated with P. multocida B:2, Group 2 with E. coli while Group 3 with M. haemolytica A:2 at 107 cfu/ml of the respective bacterium. The inoculated cell cultures were harvested at 0, 30, 60 and 120 min post-exposure and the rates of phagocytic, killing and phagocytic cell death were determined. Both phagocytosis and killing rates of all bacteria increased over incubation time. Phagocytosis involved between 71% and 73% of the neutrophils and between 60% and 64% of the macrophages at 120 min. Successful bacterial killings were shown by between 76% and 79% of the neutrophils and between 70% and 74% of the macrophages at 120 min. Death rate of the neutrophils ranged between 67% in Group 3, and 88% in Group 1 at 120 min, significantly (p<0.05) higher than Group 3 but insignificant (p>0.05) than Group 2. Similar pattern was observed for death rate of macrophages. Therefore, this study revealed that although the attachment, phagocytosis and intracellular killing rates of P. multocida B:2 were similar compared to other bacterial species used in this study, it seemed that more neutrophils and macrophages were dead following infection by P. multocida B:2 compared to E. coli and M. haemolytica A:2. Then, the endothelial cells that were obtained from the aorta of buffaloes were prepared as monolayer cell cultures. The cultures were divided into 3 groups. Group 1 was inoculated with 107 cfu/ml of whole cell P. multocida B:2, Group 2 with LPS that was extracted earlier from 107 cfu/ml of wild-type P. multocida B:2 while Group 3 with sterile cell culture medium with neither P. multocida B:2 nor LPS. The assessments on the cellular changes were done using transmission electron microscope at different points of time; at 0, 6, 12, 18, 24, 36 and 48 hours post-incubation. Groups exposed to whole cell P.multocida B:2 and LPS demonstrated moderate to severe changes, characteristic of acute cellular injury leading to cell lysis. The ultrastructural changes were consistent with necrotic changes that increased in the severity with time of incubation. There were no significant differences (p>0.05) between the two infected groups in the first 18 h post-inoculation before the severity of lesions became significant (p<0.05) thereafter. All infected groups showed significantly (p<0.05) more severe changes compared to control Group 3 from 6 h post-inoculation onwards. The severity scores by 48 h post-inoculation reached peak with score 3 for whole cell treated BAEC and score 2.8 for LPS treated BAEC. However, this study revealed that although both whole cells and LPS endotoxin showed similar moderate to severe alterations of cellular damage, it seemed that P. multocida B:2 whole cells were more potent in causing much severe damage than LPS alone. In conclusion, the in-vitro attachment and distribution of wild type P. multocida B:2 on the cells of respiratory and urinary tracts of buffalo were found to increase over time. They were comparable with septicaemic bacteria of E. coli and the respiratory bacteria of M. haemolytica A:2. Furthermore, there was positive correlation between the attachment on the surface and the distribution. Thus, this findings affirm the pathogenic role during bacterial colonization, which allows the bacterium to exert its pathogenic and immunogenic effects on the host leading to acute septicaemia. Nevertheless, P. multocida B:2 was found to have high ability to cause death of neutrophils and macrophages allowing more survival of bacterial cells with less phagocytic cells to prevent infection. Moreover, introduction of whole cell and LPS endotoxin of P. multocida B:2 leads to endothelial cells damage thus, proposed the possible mechanism of translocation of P. multocida B:2 in acute HS to allow successful translocation from the blood vessels into the tissue and vice versa.